Family Hope Program (PKH): Impact on Community Welfare in Mayasari Village, South Pamona District, Poso Regency - Akib, Karmila; Fedayyen, Muh.Yasser (Journal of Administration, Governance, and Political Issues, 2024)
This article examines the impact of the implementation of the Family Hope Program (PKH) in improving the welfare of the people of Mayasari Village, South Pamona District, Poso Regency. This study uses descriptive qualitative types and approaches. Data collection techniques are carried out through observation, interviews, and documentation. The results of this study show that the implementation of PKH in Mayasari Village, South Pamona District has an impact on the beneficiary communities in the fields of education, health, and social welfare. This PKH can reduce the burden of poor household expenses, especially helping with education and health costs, but has not been able to improve the welfare of beneficiaries. Because PKH beneficiary families are highly dependent on the assistance provided, the family's welfare has not improved. On the other hand, this program has an impact on the community outside the program, namely social jealousy The implementation of PKH in Mayasari Village also encounters several problems, namely the uneven distribution of aid because there are still many poor families who have not received assistance and the use of PKH assistance outside the education and health components as well as the lack of commitment of the recipient community in the health sector who are lazy to check their health and immunize their toddlers,  and there are some PKH beneficiary children who are lazy to go to school The continuity of this program requires a more comprehensive approach, including knowledge of financial management and the development of financial independence. In addition, community participation in government programs must also be increased so that a sense of ownership and collective responsibility to improve the standard of living is created.